Depression and its Association with Vitamin D Deficiency: A Review - Shoukry, Heba Samy (BioScientific Review, 2020)
Depression is a common psychological disorder and a major health issue. Many socioeconomic, environmental and genetic factors contribute to the onset and progression of depression. In recent years, the deficiency of vitamin D has emerged as a possible predisposing factor responsible for the manifestation of depression. In this review article, the causes of depression are briefly reviewed with a special focus on the association between vitamin D and depression. In recent years, the association between vitamin D and depression has been extensively investigated; still, the mechanism that governs this association is not fully understood. An understanding of the underlying biological processes and mechanisms through which vitamin D exerts its role will help in understanding the predisposition towards depression and the amelioration of depressive symptoms. Copyright (c) The Author